ISOLASI DAN KARAKTERISASI KITOSAN DARI KULIT UDANG WINDU (Peneaus monodon) YANG DIBUDIDAYAKAN DI GORONTALO - Usman, Anggraini Dj; Lukum, Astin; Bialangi, Nurhayati (Jurnal Entropi, 2009)
This research is a laboratory experiment, which intends to isolate and characterize chitosan of windu shrimps skin, which is cultivated in Gorontalo by using Fourier Transform Infra Red Spectrophotometer. The result of water analysis and degree, ash degree, and the degree of deasetilation, which were found were in accordance to standard parameter of chitosan which is required, that are 8%, 1,5% and 80,01%. The test of chitosan solubility characteristic was apparently in accordance with standard parameter of chitosan quality that is not soluble in water, concentrated NH3, Na2SO4 2%, slightly soluble in concentrated HCl, concentrated HNO3 and soluble in CH3COOH 1%.